A Implantação Da Controladoria E Seu Reflexo Na Operacionalidade Setorial Na Empresa ABC - Pereira, Franciellen Parlandrino (Universidade Federal do Tocantins, 2022)
This study aims to present the consequences of the implementation of controllership in the operation of the ABC company. This is an exploratory research, with a qualitative approach, classified as a case study. Data were collected through application to employees of the ABC company. As a result, it is observed that the employees understand that the controllership is responsible for the control, planning, the accounting part and for the analysis of information, in addition they understand the controllership as responsible for generating reports, making the budget planning and improving processes. Therefore, it is clear that the implementation of controllership positively affects the development of the ABC company, with the main effects being the automation of processes, greater transparency in the activities carried out, monitoring of purchasing processes, creation of routines and work standards, facilitating and training Faster as monthly services, lower rework rate report that represent the business reality with consistent and legitimate information.